Colletotrichum aotearoa B. Weir & P.R. Johnst causing leaf anthracnose in Lithocarpus litseifolius in China - Yuling Wang; Chang Liu; Guolin Cai; Ning Shu; Ziqiang Luo; Zixuan Qiu; Wuping Yan (Crop Protection, 2026)

Platinum accumulation in chemotherapy: toxicity mechanisms, challenges, and mitigation strategies - Yier Lai; Guodong Qiu; Zhiwei Zheng; Xiaoting Huang; Pi Guo; Yuling Zhang; Ling Fang (BioMetals, 2026)
Platinum-based chemotherapeutic agents constitute the cornerstone of treatment for a wide range of solid tumors. However, residual platinum can persist in the body long after treatment cessation, leading to progressive accumulation, chronic multi-system toxicity, and significant impairment of patients' quality of life. The insidious onset and lack of specific monitoring methods often lead to the oversight of this treatment-related metal accumulation toxicity. This article reviews the environmental and occupational exposure risks of platinum, its unique pharmacokinetic properties, and elucidates how its irreversible binding to proteins and accumulation within mitochondria form the chemical basis for its long-term toxicity. It further elaborates on the core mechanisms underlying platinum accumulation-mediated multi-organ toxicity, including nephrotoxicity, neurotoxicity, and ototoxicity. The aim is to provide insights and directions for improving the long-term prognosis of cancer survivors by clarifying the toxicological mechanisms, clinical impacts, and future strategies for mitigating platinum-induced metal accumulation.

Characteristics and source apportionment of atmospheric fine particulate-bound mercury (PBM2.5) in abandoned mercury mining areas in southwestern China - Yuling Kuang; Longchao Liang; Shasha Liu; Xian Dong; Fang Zhu; Xiaohang Xu; Zhuo Chen; Yayun Li; Yaji Li; Guangle Qiu (Acta Geochimica, 2026)

Mercury dynamics and speciation in paddy soils irrigated with acid mine drainage from abandoned coal mine: Insights from vertical profiling - Shasha Liu; Longchao Liang; Xiaohang Xu; Yuling Kuang; Le Wang; Guangle Qiu; Zhuo Chen; Xian Dong; Jialiang Han (Acta Geochimica, 2026)

Warming‐Induced Carbon Vulnerability in Permafrost Forests: A Shift in Q 10 From Continuous to Discontinuous Zones - Changjiang Huang; Tadeo Sáez‐Sandino; Guiyao Zhou; Lingyan Zhou; Tongyao Kong; Yuling Fu; Hongyang Chen; Yimin Zhu; Shuying Qiu; Kui Xue; Chongwei Fan; Lei Cao; et al. (Global Change Biology, 2026)
Permafrost forests harbor vast, climate‐sensitive carbon (C) reservoirs whose vulnerability largely depends on temperature sensitivity of microbial respiration ( Q 10 ). However, substantial uncertainties persist in predicting Q 10 patterns due to complex interactions among multiple ecological factors. Here, we conducted a standardized field survey with controlled incubations across a regional gradient from continuous permafrost (CP) and discontinuous permafrost (Dis‐CP, including sporadic and isolated ones) in the Greater Khingan Mountains to quantify Q 10 values and identify their main ecological controls. We found that the Q 10 values were significantly higher in CP than Dis‐CP forests, indicating a stronger microbial respiratory response to warming in the coldest permafrost regions. Statistical analysis revealed that the soil microbiome was the most important factor explaining Q 10 values in CP forest (47.8%), whereas a distinct set of factors (plant production, fine texture, substrate quality, and mean annual ground temperature) explained the largest proportion (63.2%) of Q 10 variation in Dis‐CP forests. Our findings suggest that warming‐induced permafrost degradation is likely to shift the dominant controls for Q 10 from microbial community to abiotic and plant‐related factors, while enhancing greenhouse gas emissions from permafrost soils.

Molecular design of polyoxovanadate cathodes for advanced AZIBs: Multielectron redox chemistry and structural engineering - Yu Zhang; Tiantian Guan; Fan Yang; Qing Han; Lingling Xie; Xuejing Qiu; Lei Wang; Hongjun Chen; Yuling Wang; Xiaobo Ji; Limin Zhu; Xiaoyu Cao (Chemical Engineering Journal, 2025)

Demethylase MpAlkB2 negatively regulates the growth and positively regulates the synthesis of mycotoxin citrinin in Monascus purpureus - Yuling Chen; Tiaoshuang Qiu; Yongzhong Wang; Yingwu Yang (Archives of Microbiology, 2025)

A pilot-scale study of biological activated carbon (BAC) filter for secondary effluent of petrochemical wastewater: Performance and mechanisms - Weiqing Xu; Yuling Liu; Jinkai Xue; Jie Pan; Yaozhong Zhang; Xiaopeng Qiu; Xing Zheng (Journal of Environmental Chemical Engineering, 2025)

The shifting pattern of CO2 source sink in a subtropical urbanizing lightly eutrophic lake - Rongjie Yang; Huixing Song; Qiao Qin; Yingying Chen; Di Li; Yuling Qiu; Kezhu Lu; Yike Tan; Qingqing Chen; Xinhao Cao; Shiliang Liu (Science of The Total Environment, 2024)

Nucleic acid demethylase MpAlkB1 regulates the growth, development, and secondary metabolite biosynthesis in Monascus purpureus - Tiaoshuang Qiu; Lingqing Zeng; Yuling Chen; Yingwu Yang (World Journal of Microbiology and Biotechnology, 2024)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Emotional intelligence moderates the relationship between regional gray matter volume in the bilateral temporal pole and critical thinking disposition - Xiaonan Yao; Shuge Yuan; Wenjing Yang; Qunlin Chen; Dongtao Wei; Yuling Hou; Lijie Zhang; Jiang Qiu; Dong Yang (Brain Imaging and Behavior, 2018)

Investigation on the mechanisms for biotransformation of saponins to diosgenin - Yuling Zhu; Hancan Zhu; Muqing Qiu; Tingting Zhu; Jinren Ni (World Journal of Microbiology and Biotechnology, 2014)